2022
DOI: 10.1002/term.3307
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic field modulates olfactory ensheathing cell's morphology, division, and migration activities, a biophysical approach to regeneration

Abstract: The moderate static magnetic fields (SMFs) have been used here as a non-invasive tool to study their manipulative effects on the olfactory ensheathing cells (OECs) activity, growth, morphology, and migration in culture. The OECs are involved in the regeneration of primary olfactory sensory neurons and migration into the central nervous system to repair axons damaged by infection, injury, etc., that play a pivotal role in complementary regenerative medicine. Here, OECs were isolated from the olfactory bulb and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“… 49 Exposure of rat olfactory ensheathing cells (OECs) to 30, 50, and 70 mT SMFs led to filamentous pseudopod formation, cell morphology changes and cell migration promotion. 50 Nakamichi et al discovered that 100 mT SMF considerably reduced cell proliferation of neural progenitor cells (NPCs) and promoted their differentiation into neurons. 51 Pacini et al treated normal human neuronal cells (FNC-B4) with SMF generated by 200 mT magnetic resonance tomography for 120 min, and found that SMF caused significant FNC-B4 morphology changes and promoted neural differentiation.…”
Section: Nerve Cellsmentioning
confidence: 99%
“… 49 Exposure of rat olfactory ensheathing cells (OECs) to 30, 50, and 70 mT SMFs led to filamentous pseudopod formation, cell morphology changes and cell migration promotion. 50 Nakamichi et al discovered that 100 mT SMF considerably reduced cell proliferation of neural progenitor cells (NPCs) and promoted their differentiation into neurons. 51 Pacini et al treated normal human neuronal cells (FNC-B4) with SMF generated by 200 mT magnetic resonance tomography for 120 min, and found that SMF caused significant FNC-B4 morphology changes and promoted neural differentiation.…”
Section: Nerve Cellsmentioning
confidence: 99%